History and Memory in the Novels of Gabriela Adamesteanu - Roumiana L. Stantcheva (Zeszyty Cyrylo-Metodiańskie)
The present paper analyses the novelistic work of contemporary Romanian writer Gabriela Adamesteanu (born 1942) in the context of the skepticism of historiography regarding the notion of collective memory expressed by Pierre Nora and Reinhart Koselleck. Examples from her six novels highlight the intentional use of historical events as a backdrop for characters’ ideological clashes and for the expression of group beliefs, fictional versions of collective memory. The analysis reveals how the narratological hesitation, the intensive use of dialogues and the semi-direct speech build up the psychological density of the writer’s works. The study shows that Adamesteanu’s thematic polyphony reveals the individual memory of the characters as a testimony of the public memory of separate groups, some of them sharing a more modern worldview, while others preserving traditional stances. Original title in Bulgarian: История и памет в романите на Габриела Адамещяну.